Differential effects of resource availability and usage on learning, achievement, and subjective well-being - Harder, Bettina (Cogent Education, 2025)
Resources play a crucial role in developmental processes. However, assessments often fail to distinguish between resource availability and their active use in driving change or sustaining a system state, even though possessing resources should not be sufficient to achieve desired outcomes. This article systematically compares resource availability versus usage for the first time, drawing on the theory of educational and learning capital (Ziegler & Baker, 2013) and examining their correlates across two studies. Study 1 (N = 64 university students, 87.5% female, Mage = 23.3 years) analyzed the relationship between resource facets, self-regulation of the learning process, and implemented learning strategies. Study 2 (N = 120 Ph.D. students, 40% female, Mage = 28.43 years) examined the resource facets in relation to deliberate practice, academic achievement, adaptation to their field (DILA), and subjective well-being. Results from Study 1 highlighted the importance of utilizing environmental resources in the learning process. In Study 2, usage did not dominate predictions of learning and achievement, while results also indicated that subjective well-being depended more on resource availability, possibly because gathering resources provides security in the face of anticipated life challenges. These findings provide new insights into resource dynamics and directions for future research.
CRIS-Team Scopus Importer:2025-05-23
Keywords: achievement; Adult Education and Lifelong Learning; Education - Social Sciences; educational and learning capital; Educational Psychology; Higher Education; learning; Resources; subjective well-being; Teachers & Teacher Education; Theories of Learning